2020
DOI: 10.1038/s41598-020-63822-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hypodynamic Change of Cerebrospinal Fluid Flow as A Potential Factor Working for Experimental Scoliotic Formation

Abstract: Scoliosis is often associated with syringomyelia (SM). As an important role in SM formation, the influence from abnormal cerebrospinal fluid (CSF) flow is still unclear to scoliosis. The aim of this experimental work is to explore the connection between CSF flow and scoliosis through imaging and histological analysis on the basis of a kaolin-induced scoliotic rabbit model. For imaging observation, in 40 kaolin-induced rabbits by C7 spinal cord injection, through pre-and postoperative MRI and radiography, CSF f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In experimental studies, cerebrospinal fluid (CSF) flow changes and abnormal cilia motility were found and related to spinal deformity and scoliosis [6,7]. Also, protein tyrosine kinase 7 (ptk7) gene mutation causes scoliosis in the zebrafish model [4].…”
Section: Advances In Knowledgementioning
confidence: 99%
“…In experimental studies, cerebrospinal fluid (CSF) flow changes and abnormal cilia motility were found and related to spinal deformity and scoliosis [6,7]. Also, protein tyrosine kinase 7 (ptk7) gene mutation causes scoliosis in the zebrafish model [4].…”
Section: Advances In Knowledgementioning
confidence: 99%
“…It is well known that the improper curvature of the spin seen in scoliosis patients can cause obstructed cerebrospinal fluid (CSF) flow from the spine to the brain. 28 Furthermore, CSF is rich in various growth factors such as vascular endothelial growth factor (VEGF), epidermal growth factor (EGF) and platelet-derived growth factor (PDGF), all of which have been shown to be elevated in the CSF in different malignant brain neoplasms. [29][30][31] The obstructed CSF flow caused by scoliosis in NF1 patients may be preventing the proper circulation of these growth factors to the brain and its associated neoplasm, decreasing the likelihood of the development of a malignant neurological neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity analysis demonstrated that NF1 patients with scoliosis were at a lower risk for developing malignant neurological neoplasms. It is well known that the improper curvature of the spin seen in scoliosis patients can cause obstructed cerebrospinal fluid (CSF) flow from the spine to the brain 28 . Furthermore, CSF is rich in various growth factors such as vascular endothelial growth factor (VEGF), epidermal growth factor (EGF) and platelet‐derived growth factor (PDGF), all of which have been shown to be elevated in the CSF in different malignant brain neoplasms 29–31 .…”
Section: Discussionmentioning
confidence: 99%
“…32 Additionally, CSF flow alterations have been identified as a potential initiator for the development of spinal deformity. 64 However, further research is needed to investigate and better elucidate the underlying mechanisms of spinal deformity development and propagation in children with Chiari I malformations.…”
Section: Influence Of Intraspinal Anomaly On Spinal Deformitymentioning
confidence: 99%